Ambrosia gall midges (Diptera: Cecidomyiidae) and their microbial symbionts as a neglected model of fungus-farming evolution - Pyszko, Petr; Šigutová, Hana; Ševčík, Jan; Drgová, Michaela; Hařovská, Denisa; Drozd, Pavel (FEMS microbiology reviews, 2025)
Ambrosia gall midges (AGMs) represent an intriguing group within the Cecidomyiidae, one of the most diversified dipteran families. AGMs form galls on plants, where they cultivate and consume fungal symbionts (phytomycetophagy). This mutualistic relationship may play a critical role in larval nutrition, gall morphogenesis, and protection against natural enemies. Although most other fungus-farming taxa have been intensively studied, AGMs have largely been neglected. This review synthesizes current knowledge on the diversity, biology, and ecological interactions of AGM, highlighting the intricate relationships with their fungal symbionts. The implications for adaptive radiation and speciation are critically considered, including how fungal associations may have facilitated ecological flexibility and diversification. We also tackle the processes of coevolution, not only between AGM and their fungal symbionts but also involving plants and parasitoids. We identify the most pressing issues and discrepancies in the current understanding the AGM-fungi interactions. Key areas of future research should include elucidating fungal acquisition and transmission mechanisms, determining the specificity and diversity of AGM-associated fungal communities, understanding the evolutionary pathways leading to phytomycetophagy, and addressing taxonomic challenges within the AGM group, where species identification has been complicated by reliance on gall morphology and host specificity.
Keywords: symbióza; nádory rostlin; fungal symbionts; host shift; Fungi; houby; Symbiosis; Animals; biologická evoluce; fungus farming; Plant Tumors; Diptera; Biological Evolution; ambrosia gall midges; host specialization; phytomycetophagy; zvířata